CONDITIONS OF WORK AND MAIN REQUIREMENTS TO THE MATERIAL OF THE CYLINDER BLOCK SLUGS - A. N. Krutilin; M. I. Kurbatov; M. I. Kurbatova (Литьë и металлургия, 2005)
The conditions of work and main requirements to material of the cylinders block liners are given.